Influence of early life management strategies on indicators of health and performance in pre-weaned dairy calves and mature cows - Velasquez Munoz, Ana Karina, author; Pinedo, Pablo, advisor; Lombard, Jason, committee member; Rao, Sangeeta, committee member; Roman Muniz, Ivette Noami, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: behavior; first lactation; immunity; dairy cow; dairy calf; health